Learning about depression by watching gaming videos: a case study on the potential of digital games for psychoeducation and destigmatization - Rüth, Marco; Bachmayer, Raoul; Kaspar, Kai (Frontiers in Psychology, 2025)
IntroductionPeople with depression can also suffer from stigmatization related to depression. Psychoeducation is one way to alleviate stigmatization (destigmatization), so that particularly people without depression become more aware of depressive symptoms and can empathize better with depressed people. Here, we scrutinize the potential of digital games to support psychoeducation and destigmatization of depression.MethodsWe conducted a mixed methods online study with 117 participants. In the intervention phase, participants watched gaming videos and noted down aspects that had left a lasting impression on them. In the evaluation phase, we used open-ended items and qualitative content analysis to investigate participants’ learning outcomes. We used quantitative scales to examine different facets of participants’ learning motivation, their narrative engagement, and destigmatization types.ResultsWatching gaming videos resulted in several learning outcomes, including cognitive as well as emotional effects. Given a high general learning motivation regarding the topic depression and moderate narrative engagement in our sample, participants also reported strong conviction that such games can be an interesting and relevant medium to learn about depression. A multiple regression analysis revealed that 51% of variance in participants’ personal thoughts about depression could be explained by our proposed model. Males had a higher personal stigma than females. Personal stigma was also negatively related to participants’ depression literacy and their general learning motivation regarding the topic depression.DiscussionOur findings indicate that watching videos of digital games can support psychoeducation and destigmatization by reaching a broad audience and sensitizing people about mental illnesses such as depression.